Phenolic Extract from Moringa oleifera Leaves Inhibits Key Enzymes Linked to Erectile Dysfunction and Oxidative Stress in Rats’ Penile Tissues - Ganiyu Oboh; Adedayo O. Ademiluyi; Ayokunle O. Ademosun; Tosin A. Olasehinde; Sunday I. Oyeleye; Aline A. Boligon; Margareth L. Athayde (Biochemistry Research International)
This study was designed to determine the antioxidant properties and inhibitory effects of extract from Moringa oleifera leaves on angiotensin-I-converting enzyme (ACE) and arginase activities in vitro. The extract was prepared and phenolic (total phenols and flavonoid) contents, radical (nitric oxide (NO), hydroxyl (OH)) scavenging abilities, and Fe2+-chelating ability were assessed. Characterization of the phenolic constituents was done via high performance liquid chromatography-diode array detection (HPLC-DAD) analysis. Furthermore, the effects of the extract on Fe2+-induced MDA production in rats’ penile tissue homogenate as well as its action on ACE and arginase activities were also determined. The extract scavenged NO∗, OH∗, chelated Fe2+, and inhibited MDA production in a dose-dependent pattern with IC50 values of 1.36, 0.52, and 0.38 mg/mL and 194.23 µg/mL, respectively. Gallic acid, chlorogenic acid, quercetin, and kaempferol were the most abundant phenolic compounds identified in the leaf extract. The extract also inhibited ACE and arginase activities in a dose-dependent pattern and their IC50 values were 303.03 and 159.59 µg/mL, respectively. The phenolic contents, inhibition of ACE, arginase, and Fe2+-induced MDA production, and radical (OH∗, NO∗) scavenging and Fe2+-chelating abilities could be some of the possible mechanisms by which M. oleifera leaves could be used in the treatment and/or management of erectile dysfunction.